Molecular cloning and chromosomal localization of the murine homolog of the human helix-loop-helix gene SCL. - Begley, C G (1991)
The human SCL gene is a member of the family of genes that encode the helix-loop-helix (HLH) class of DNA-binding proteins. A murine SCL cDNA was isolated from a normal macrophage cDNA library by using HLH-specific oligonucleotides as hybridization probes. The coding region is 987 base pairs and encodes a predicted protein of 34 kDa. The nucleotide sequence of the coding region shows 88% identity to the human SCL gene, and the amino acid sequence is 94% identical. The HLH motif and upstream hydrophilic region are entirely conserved in the murine and human proteins. The identity between the mouse and human sequences was less marked in the 5' and 3' untranslated regions. Two murine SCL transcripts that differ in the 3' noncoding region have been detected in fetal liver and various cell lines. Variation was also observed in the 5' untranslated region. Interestingly, immediately downstream of the protein-termination codon, both the human SCL sequence and the murine homolog share an E-box element--the suggested target site for DNA binding of HLH proteins. The murine SCL homolog was mapped to the central part of chromosome 4.